Easy to Read : Young Cam Jansen and the Library Mystery - Adler, David A.; Natti, Susanna (New York, 2001)
Cam uses her photographic memory to find a shopping list that her dad lost at the library.
"Grades K-2"--P. [4] of cover.
"Ages 5-8"--P. [4] of cover.
Keywords: Memory; Fiction; Mystery and detective stories; Easy Reader